"Maternal Impressions": Disability Memoirs in Socialist Poland. Issue 1 (1st March 2019) - Pamula, Natalia
Abstract : This article discusses disability memoirs written by mothers of disabled sons during state socialism in Poland. It recovers an often forgotten experience of living socialism as a mother of a disabled child and analyzes disability as a category of difference that, unlike gender or class, was not reordered by the socialist state. It argues that disability reconfigured motherhood as a political institution under state socialism and shows that a child's disability permitted women to become politically disobedient subjects. Disability allowed women who were responsible for their children's overcoming disability to make demands on the state and criticize it for the lack of sufficient accommodations and resources. At the same time, the article highlights the violence embedded in the relationship between a disabled son and his mother.